Timing of invasive treatment after fibrinolysis in ST elevation myocardial infarction--a meta-analysis of immediate or early routine versus deferred or ischemia-guided randomised controlled trials. - Desch, S; Eitel, I; Rahimi, K; de Waha, S; Schuler, G; Thiele, H (2010)
CONTEXT: Controversy remains over the optimal timing of percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI) who have initially been treated with fibrinolytic agents. OBJECTIVE: A meta-analysis of studies was performed comparing immediate or early angiography after fibrinolysis versus a more conservative strategy of deferred PCI or ischaemia-guided management. Data sources MEDLINE, EMBASE, CENTRAL, ClinicalTrials.gov Study selection Nine contemporary randomised controlled trials eligible for inclusion enrolling a total of 3325 patients were identified. Follow-up ranged between 1 and 12 months. DATA EXTRACTION: Data were extracted by two independent reviewers using a standard form and cross-checked. Results There was suggestive evidence for a reduction in the risk of total mortality in patients undergoing immediate or early PCI. There were no significant differences in the risk of stroke or major bleeding. Conclusions These results support the current recommendation of a routine early invasive strategy in STEMI patients after successful fibrinolysis.